Analisis Praktik Citizen Journalism pada Akun Twitter Merapi Uncover dalam Menerapkan Kode Etik Jurnalistik - Dwi Pela Agustina; Lugas Jatmiko Adi (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2023)
Advances in technology accompanied by the rapid development of social media have made it easier for people to disseminate information, from writing, reporting, to disseminating the information they encounter in everyday life. In producing information, an understanding of the journalistic code of ethics is needed so that the content shared does not create new conflicts in society. This research was conducted to find out how the journalistic code of ethics is applied to the Merapi Uncover Twitter account as a citizen journalism media. This research is a descriptive qualitative research, namely research that will describe, describe, explain, explain, or answer in more detail the existing problems. The following research results are obtained: (1) Merapi Uncover is included in citizen journalism because the information shared is a product of non-journalist citizens. (2) Merapi Uncover tries to apply journalistic elements, such as using the 5W+1H (What, Who, Where, When, Why, and How) writing guidelines. (3) Information produced by Merapi Uncover is prone to subpoenas, because the information produced is not always guided by a journalistic code of ethics.